2019
DOI: 10.1002/stem.3007
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Overexpression in Mesenchymal Stem Cells Exerts Antiaging and Antiosteoporosis Effects by Inactivating p16/p19 Signaling and Inhibiting Oxidative Stress

Abstract: We previously demonstrated that Bmi1 deficiency leads to osteoporosis phenotype by inhibiting the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells (MSCs), but it is unclear whether overexpression of Bmi1 in MSCs stimulates skeletal development and rescues Bmi1 deficiency‐induced osteoporosis. To answer this question, we constructed transgenic mice (Bmi1Tg) that overexpressed Bmi1 driven by the Prx1 gene and analyzed their skeletal phenotype differences with that of wild‐type l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…We have previously reported that Bmi1 deficiency‐induced osteoporosis was caused by the impaired proliferation of BM‐MSCs and activation of the p16 Ink4a /p19 Arf signaling pathway . Recently we generated transgenic mice overexpressing Bmi1 in MSCs (driven by the Prx1 gene) and showed that overexpression of Bmi1 in MSCs stimulated osteogenesis of BM‐MSCs, accelerated skeletal growth and increased bone mass . In the current study, we generated Cyp27b1 +/− mice with Bmi1 overexpression in MSCs.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…We have previously reported that Bmi1 deficiency‐induced osteoporosis was caused by the impaired proliferation of BM‐MSCs and activation of the p16 Ink4a /p19 Arf signaling pathway . Recently we generated transgenic mice overexpressing Bmi1 in MSCs (driven by the Prx1 gene) and showed that overexpression of Bmi1 in MSCs stimulated osteogenesis of BM‐MSCs, accelerated skeletal growth and increased bone mass . In the current study, we generated Cyp27b1 +/− mice with Bmi1 overexpression in MSCs.…”
Section: Discussionmentioning
confidence: 85%
“…The Cyp27b1 +/− mice, originally on a BALB/c background, were repeatedly backcrossed with WT mice on a C57BL/6J background for over 12 generations to obtain Cyp27b1 +/− mice on a C57BL/6J background. Bmi1 Tg mice that highly express Bmi1 under the control of a 2.4‐kilobase (kb) Prx1 promoter were generated in Nanjing Medical University (Nanjing, China), and genotyped by PCR as described . Bmi1 Tg mice were maintained on a C57BL/6J genetic background.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations